2016
DOI: 10.1186/s12887-016-0573-2
|View full text |Cite
|
Sign up to set email alerts
|

The large contribution of twins to neonatal and post-neonatal mortality in The Gambia, a 5-year prospective study

Abstract: BackgroundA high twinning rate and an increased risk of mortality among twins contribute to the high burden of infant mortality in Africa. This study examined the contribution of twins to neonatal and post-neonatal mortality in The Gambia, and evaluated factors that contribute to the excess mortality among twins.MethodsWe analysed data from the Basse Health and Demographic Surveillance System (BHDSS) collected from January 2009 to December 2013. Demographic and epidemiological variables were assessed for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 33 publications
5
21
0
3
Order By: Relevance
“…21 The greater risk of death in infants from multiple pregnancies, compared to infants of single pregnancies, as well as higher rates of preterm births and low birth weight, and a higher number of complications in pregnancy and childbirth, has also been reported in previous studies. 22,23 Our study found higher mortality rates on the first day of life among indigenous children. This finding is in keeping with reports found in previous studies, according to which higher early and late neonatal mortality rates were found in LB with this ethnicity/skin color for Brazil as a whole.…”
Section: Discussionmentioning
confidence: 46%
“…21 The greater risk of death in infants from multiple pregnancies, compared to infants of single pregnancies, as well as higher rates of preterm births and low birth weight, and a higher number of complications in pregnancy and childbirth, has also been reported in previous studies. 22,23 Our study found higher mortality rates on the first day of life among indigenous children. This finding is in keeping with reports found in previous studies, according to which higher early and late neonatal mortality rates were found in LB with this ethnicity/skin color for Brazil as a whole.…”
Section: Discussionmentioning
confidence: 46%
“…7 If possible, home visits by health professionals should be undertaken during the first year of life to identify twins failing to thrive. 6,7 In Guinea-Bissau, we found that birthweight less than 2000 g, death of the co-twin perinatally, and severe maternal illness during pregnancy were risk factors for twin death in the first months after birth. 6 Finally, more research is needed regarding obstacles to hospital admissions for twins.…”
Section: Twin-singleton Early-life Survival In Sub-saharan Africamentioning
confidence: 99%
“…This relatively large number of twins may contribute substantially to perinatal mortality in the region [11]. Increased prevalence of preterm delivery and low-birth weight among twins leads to increased risk of under-five mortality due to malnutrition, respiratory disorders, vulnerability to infection, and developmental delays [12,13]. It is estimated that one in five twins born in sub-Saharan Africa dies before the age of five [11].…”
Section: Introductionmentioning
confidence: 99%